Subgenomic Diversity Patterns Caused by Directional Selection in Bread Wheat Gene Pools. Issue 2 (1st July 2015) - Voss‐Fels, Kai; Frisch, Matthias; Qian, Lunwen; Kontowski, Stefan; Friedt, Wolfgang; Gottwald, Sven; Snowdon, Rod J.
Abstract : Genetic diversity represents the fundamental key to breeding success, providing the basis for breeders to select varieties with constantly improving yield performance. On the other hand, strong selection during domestication and breeding have eliminated considerable genetic diversity in the breeding pools of major crops, causing erosion of genetic potential for adaptation to emerging challenges like climate change. High‐throughput genomic technologies can address this dilemma by providing detailed knowledge to characterize and replenish genetic diversity in breeding programs. In hexaploid bread wheat ( Triticum aestivum L.), the staple food for 35% of the world's population, bottlenecks during allopolyploidisation followed by strong artificial selection have considerably narrowed diversity to the extent that yields in many regions appear to be unexpectedly stagnating. In this study, we used a 90, 000 single nucleotide polymorphism (SNP) wheat genotyping array to assay high‐frequency, polymorphic SNP markers in 460 accessions representing different phenological diversity groups from Asian, Australian, European, and North American bread wheat breeding materials. Detailed analysis of subgroup diversity at the chromosome and subgenome scale revealed highly distinct patterns of conserved linkage disequilibrium between different gene pools. The data enable identification of genome regions in most need of rejuvenation with novel diversity and provide a high‐resolution molecular basis for genomic‐assisted introgression of new variation into chromosome segments surrounding directionally selected metaloci conferring important adaptation and quality traits.